Design and test of the plant-correcting reel for harvesting lodging garlic plants - Li, Yuhua; Li, Chao; Liu, Lupeng; Zhou, Kai; Hou, Jialin (International Journal of Agricultural and Biological Engineering, 2024)
Crops are prone to lodging with the decline of stem moisture and the intervention of other factors in the mature harvest period, such as garlic, which is difficult to harvest mechanically. To solve this problem, the plant-correcting reel for harvesting lodging garlic plants, bumped and deformed with plants many times to pull and lift them into a conveyor, is proposed in this study. We analyzed the motion trajectory equation and key influencing factors of the reel and defined the lifting and plant-correcting stages as three processes of contact, stirring and release. For example, the contact deformation model and system energy equations were established in the contact process. Besides, in the stirring process, the garlic plant-correcting conditions were established through the dynamic simulation test analysis of garlic seedling trajectories and the deflection model of garlic stem was constructed. Furthermore, in the release process, the expressions of rubber bars rotation and garlic plant offset bending curvature were constructed and the optimal number and distribution form of bars were determined. Meanwhile, the mechanism and key operating parameters of the auxiliary lifting mechanism of the divider were established. Through the single-factor test, the influence of reel speed, forward speed and reel height on the success feeding rate was analyzed under different bars distribution forms; Through multi-factor experiments, the interaction contour map of various factors was constructed. When reel speed, forward speed and reel height were 3 rad/s, 3.5 m/s, and 540 mm, the feeding success rate was 98.73%. The optimization factors were tested and verified, which met the operational requirements of a high feeding success rate and low loss rate of garlic harvest. This study combines laboratory virtual as well as field experiments and analyzes of trajectory of bars, contact deformation and deflection model of garlic plant, and reel rotation and garlic plant offset bending curvature to solve the problem of garlic lodging mechanized harvest and yield reduction. Keywords: feeding success rate, lodging; garlic, harvesting reel, plant model, field test DOI: 10.25165/j.ijabe.20241701.7784 Citation: Li Y H, Li C, Liu L P, Zhou K, Hou J L. Design and test of the plant-correcting reel for harvesting lodging garlic plants. Int J Agric & Biol Eng, 2024; 17(1): 59-68.